Building from the Periphery: Tracing the Implementation of Infrastructure Development Policy in the Jagoi Babang Borderlands - Hartati; Sofyan Cholid (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study intends to analyze the implementation of infrastructure development policies in the Jagoi Babang border area using the Van Meter and Van Horn model, which emphasizes six policy implementation variables. The research method used is descriptive qualitative, with data collection techniques through documentation studies, field observations, and in-depth interviews with stakeholders at the local and central levels. Border areas are strategic areas that reflect the state's presence in aspects of sovereignty, public services, and community welfare. Nevertheless, infrastructure development in border areas like Jagoi Babang, Bengkayang Regency, West Kalimantan, still faces numerous implementation challenges. The results show that policy implementation faces structural barriers such as weak inter-agency coordination, limited resources, and budget rigidities, as well as cultural barriers in the form of minimal community participation, low sense of ownership, and neglect of local values. The research recommends an improvement strategy that includes local context-based policy adjustments, strengthening cross-sectoral coordination, budget reform, and community empowerment. The findings are significant in encouraging the formulation of border development policies that are more inclusive, adaptive and sustainable, and provide a conceptual contribution to strengthening policy implementation capacity in other underdeveloped and strategic areas